Security in The Transforming World: Balancing Traditional and Non-Traditional Threats - Dr. Arfan Mahmood; Muhammad Tahir; Maryam Arshad Tarar (Social Science Review Archives, 2025)
Twenty-first-century security is reshaped by a concept that expands defense by military means to include political stability, economic prosperity, human rights, and social justice. Interstate war and frontier war contrasted with traditional vs. non-traditional threats of terrorism, extremism, economic marginalization, pandemics, environmental insecurity, and state failure. The management of conventional and non-conventional threats from state to state is addressed in this article through a multidisciplinary approach. There are five highest order points of concern in the Human Security Paradigm and the Conflict Transformation Theory, and these are: economic development, protection of rights and removal of deprivations, political negotiation as the highest order point of concern, reintegration of the opposition dissident of the national society, and upholding the rule of law. Given the South African, Colombian, Pakistani, and Nepali experiences through a qualitative case study with thematic analysis, the study arrives at the conclusion that exclusive reliance on the exercise of military power can never amount to a guarantee of long-term stability. Rather, people-centered, participatory approaches have to be engaged in attempting to deal with the causes of insecurity at their source. The last observation to be made from the paper is that the new world is founded on political, social, economic, and legal strategy and customary defense institutions uniting for the sake of discovering lasting peace.